ISOLASI DAN KARAKTERISASI YEAST AMILOLITIK DARI RAGI TAPE - Nurhartadi, Edhi; Rahayu, Endang Sutriswati (Universitas Sebelas Maret (UNS), 2011)
The demand of sugar increases every year caused by people growth. Indonesia has starchy materialslike tapioca and for long time used to produce food by traditional fermentation with ragi tape. Ragi tapecontains many amylolytic and fermentative microbial. The object of this study was to isolate amylolytic yeastfrom ragi tape, which could be used to produce amylolytic enzymes as an alternative source of amylolyticenzyme from microbial origin. Isolation was done by dilution and spread plate methods on peptone glucoseyeast extract soluble starch (PGYS) agar medium, incubated 30C, for 2 days and purified with same medium.The isolates were then identified based on morphology and physiology profiles. Selection of the strongest isolatewith high amylolytic potent was done with amylolytic activity. The chosen isolate was then used to produceamylolytic enzyme in yeast extract malt extract soluble starch (YMS) medium with variation of soluble starchcontent. 15 amylolytic yeast isolates have been isolated, and then identified with taxonomic keys were suspectedas Debaryomyces vanriji (4 isolates), Saccharomycopsis fibuligera (3 isolates), and Pichia burtonii (8 isolates).They could grow well on starch medium. The result of selection based on amylolytic activity showed that S.fibuligera E-3 was the strongest among the others. From the fermentation, this research obtained the cellscontent increased or obtained logarithmic phase in 1st day of fermentation, and after 2nd day reached stationaryphase medium. The reduction sugar content increased in 1st day of fermentation, after 2nd day was increasedslowly. The soluble starch content was decreased rapidly in 1st day, after 2nd day was decreased slowly. Theglucoamylase activity was high at 1st day, but in 2nd day was low. S. fibuligera had glucoamylase activity 44.13mg glucose/L/min/1 ml enzyme solution.